2000
DOI: 10.1007/s002160000588
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate analysis by high-performance anion-exchange chromatography with pulsed amperometric detection: The potential is still growing

Abstract: This article reviews recent advances of carbohydrate analysis by high-performance anion-exchange chromatography with pulsed amperometric detection. Starting from the paper of Dennis C. Johnson [1] in which the great analytical promise of such a technique was anticipated, a multitude of exciting new research possibilities have recently emerged. The great attractiveness of high-performance anion-exchange chromatography is largely due to its compatibility with such a sensitive, selective and reliable detection me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(136 citation statements)
references
References 2 publications
0
132
0
4
Order By: Relevance
“…A number of authors have reported the use of HPAEC-PAD 16 for the separation of monosaccharides derived from plant and microbial sources. As a starting point, conditions similar to those reported by the instrument manufacturers were employed and involved eluting the analytes through a CarboPac PA20 column using sodium hydroxide as a mobile phase.…”
Section: Development Of An Analytical Methods Based On Hpaecmentioning
confidence: 99%
“…A number of authors have reported the use of HPAEC-PAD 16 for the separation of monosaccharides derived from plant and microbial sources. As a starting point, conditions similar to those reported by the instrument manufacturers were employed and involved eluting the analytes through a CarboPac PA20 column using sodium hydroxide as a mobile phase.…”
Section: Development Of An Analytical Methods Based On Hpaecmentioning
confidence: 99%
“…127 The CarboPac columns from Dionex are packed with latex-type stationary phases consisting of sulfonatepolystyrene divinylbenzene resin (10 μm diameter) with a layer of porous beads (0.1 μm diameter) with quaternary ammonium groups, enabling anion-exchange chromatography. Sugars are eluted using concentration gradients of a sodium hydroxide/ sodium acetate system.…”
Section: ·4 High-performance (High-ph) Anion-exchange Chromatographymentioning
confidence: 99%
“…For nonreducing sugars such as glycosides, this can be explained considering that they cannot be subjected to the typical derivatization strategies based on reductive amination. For reducing sugars, the development of reliable and rapid methodologies requiring limited pretreatment steps is probably necessary for competing with well-assessed chromatographic methodologies like highperformance anion-exchange LC with pulsed amperometric detection (HPAEC-PAD) [82,83], which is widely applied for the exceptionally sensitive analysis of underivatized sugars in foods but does not provide the structural information achievable with MS detection.…”
Section: Analysis Of Carbohydrates In Nutritionmentioning
confidence: 99%